Phonological Aspect on First Language Acquisition - Purnama Rika Perdana; Anida Susanti (Merwinspy Publisher, 2023)
This study aims to investigate first language acquisition on children aged 18 months with a focus on phonological aspect. The research method used is descriptive-qualitative approach. Data was collected through interviews, observation, and documentation. The observation results show that children at this age begin to master phonemes and can pronounce certain words. This study also examines the development of vowel and consonant phonemes in a child named S.S. The results show that S.S. can pronounce the vowel phonemes /a/, /i/, /u/, and /e/, but has difficulty with the vowel phoneme /o/. S.S. can also pronounce consonant phonemes /b, d, ŋ, h, j, k, l, m, n, p, s, t, y/. The role of S.S. mothers in helping language development is very important through interaction, playing, and repeating sentences. There are no significant barriers to S.S. language development, and media such as nursery rhymes and YouTube Kids are used to assist along the process. It is concluded that at the age of 18 months, children begin to master phonemes and can pronounce words. The role of parents, especially mothers, is very important in helping children to acquire language by interacting and using appropriate media.